1994
DOI: 10.1071/mf9941481
|View full text |Cite
|
Sign up to set email alerts
|

Ludwigia peruviana (Onagraceae) in the Botany Wetlands near Sydney, Australia

Abstract: Ludwigia peruviana is an aquatic shrubby species introduced from the Americas and spreading to wetlands in coastal south-eastem Australia. It has become dominant, replacing much of the former vegetation in the Botany Wetlands, a series of shallow urban swamps and lakes near Sydney, Australia. Studies of L. peruviana were essential to the development of a management plan for the Botany Wetlands. Ecological studies were conducted in situ and supplemented by a series of germination and growth experiments in contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…Ludwigia leptocarpa is an annual or short-lived perennial shrub (Dolan and Sharitz 1984) but the exotic L. peruviana is an aggressive weedy species that can form dense thickets in wetland habitats (Jacobs et al 1994). Causes for the sudden expansion of L. peruviana are not clear, but it is abundant in the seedbank of some relict wetlands on the channelized floodplain, including the Pool C BLM (Arnold van der Valk, unpublished data).…”
Section: Pool C Blmmentioning
confidence: 98%
“…Ludwigia leptocarpa is an annual or short-lived perennial shrub (Dolan and Sharitz 1984) but the exotic L. peruviana is an aggressive weedy species that can form dense thickets in wetland habitats (Jacobs et al 1994). Causes for the sudden expansion of L. peruviana are not clear, but it is abundant in the seedbank of some relict wetlands on the channelized floodplain, including the Pool C BLM (Arnold van der Valk, unpublished data).…”
Section: Pool C Blmmentioning
confidence: 98%
“…According to some authors, L. peruviana originated in the Americas (Ramamoorthy & Zardini, 1987) and later introduced into wet areas in different regions, making it a dominant species in a short period of time and an important source of floral resources for pollinators, especially for bees (Jacobs et al, 1994).…”
mentioning
confidence: 99%
“…In other locations, different species of Ludwigia can show flowering peaks in other months: Ludwigia suffruticosa (L.) Gomez flowered in winter (June) in Minas Gerais (Martins & Antonini, 1994), while Jacobs et al (1994) observed that Ludwigia peruviana (L.) Hara, recently introduced into Sidney, Australia, had its flowering peak at the beginning of autumn.…”
Section: Ludwigia Elegansmentioning
confidence: 99%